ANALISIS PENGHIDUPAN ORANG RIMBA DI KECAMATAN AIR HITAM PASCA PERUBAHAN ZONASI TAMAN NASIONAL BUKIT DUABELAS: Analysis of Orang Rimba Livelihoods in Air Hitam District Post-Zoning Reclassification of Bukit Duabelas National Park (Jurnal ForestrIndo, 2025)
In 2019, Bukit Duabelas National Park integrates its zoning system with the Orang Rimba traditional land utilization in attempt to fulfill its mandate to protect Orang Rimba’s livelihood. This research aims to determine wheter the zoning system of Bukit Duabelas National Park has truly accomodated sustainable livelihoods for Orang Rimba by exploring the livelihood resources and livelihood strategies of the Orang Rimba in Air Hitam using mixed methods and the Sustainabe Rural Livelihood framework. The research reveal different capital possession accross nomadic, semi-sedentary, and sedentary groups. Sedentary group possess highest capital across all types, except social. Livelihood strategies have shifted to cultivation (especially oil palm and rubber) with hunting-gathering primarily done by nomadic and semi-sedentary group. Non-agricultural diversification practiced only by semi-sedentary and sedentary group. This change is driven by the need for stable income, declining forest resources, and increased competition. Orang Rimba hold access, withdrawal, and management rights to Bukit Duabelas National Park. Orang Rimba's access mechanism is legal access via social identity, while individual benefits depend more on capital access. To enhance the adaptability of the Orang Rimba, implementing intercropping or optimized weeding is recommended for hunting-gathering communities, while crop diversification or integrated crop-livestock farming is suggested for groups engaged in oil palm cultivation. Furthermore, improving access to education and training is crucial to boost human capital, which is vital for opening up non-agricultural diversification opportunities.